Translational Challenges Of Robotics Terminology In English And Uzbek Languages - Rasulova Gulmira Xursanbek Gizi (Review of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to explore the translational challenges of robotics terminology between English and Uzbek from a functional-semantic perspective, focusing on the structural, conceptual, and contextual factors influencing accuracy and clarity. As robotics terminology expands globally, the absence of direct Uzbek equivalents often causes inconsistencies and ambiguity in translation. Research methodology: A qualitative descriptive approach was employed, combining linguistic comparison, corpus-based analysis of robotics texts, and expert interviews with translators and engineers. The study analyzed key robotics terms such as robot, sensor, actuator, and artificial intelligence to identify patterns of borrowing, calquing, and descriptive translation, and to evaluate their semantic and functional adequacy. Results: Findings reveal that borrowing is the most frequently used strategy due to the absence of native equivalents, but it often leads to semantic opacity for general audiences. Calquing and descriptive translation provide conceptual clarity but may distort the technical precision of original terms. The study highlights the inconsistency in current usage and the need for terminological harmonization in academic and technical contexts. Conclusions: Developing a standardized terminology framework through collaboration between linguists and robotics experts is essential to ensure linguistic accuracy, conceptual consistency, and educational effectiveness in the Uzbek language. Limitations: The research focuses on a limited set of high-frequency terms and does not include quantitative corpus statistics or cross-regional lexical variations. Contribution: This study contributes to applied linguistics and technical translation studies by offering a model for analyzing and standardizing specialized terminology in emerging scientific fields.